QTc prolongation - a predictor for autonomic neuropathy in diabetic patients - Singh Kanwar, Gopal; Paikra, Shashi; Basan, kamaljit (International Journal of Medical Research and Review, 2015)
Introduction: ECG is an important tool to assess the electrical activity of the heart. It is like any other investigation which can be done on bedside. In this study we have assessed the prolongation of QT interval (QTc), which is a marker for assessment of autonomic neuropathy (AN), in diabetic patients. The probability of autonomic neuropathy is high if the QT interval is prolonged. Material and Methods: All patients of Type I and Type II Diabetes Mellitus of various age groups studied in the period of 1 year. Results: As per the discussion QTc can be considered as the predictor of autonomic neuropathy (AN) in a patient if it is prolonged (>440 msec.). Conclusion:Instead of doing the tests for AN which are more cumbersome a simple QTc can predict AN in a patient. The thumb rule tests definitely stand to grade and assess the AN in a patient, but QTc is inexpensive, more tolerated and easier tool to label the patient as having AN.